2020
DOI: 10.2217/nmt-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Patisiran With Transthyretin Stabilizers in Patients With Hereditary transthyretin-mediated Amyloidosis

Abstract: Aim: Examine safety and pharmacodynamics of patisiran alone or with concomitant transthyretin stabilizers from the Phase II open-label extension study and safety and efficacy of patisiran in patients with prior transthyretin stabilizer use from the Phase III APOLLO study. Patients & methods: Post hoc analyses in patients with hereditary transthyretin-mediated amyloidosis with polyneuropathy. Results: Patisiran safety was consistent regardless of concomitant or prior transthyretin stabilizers. In the Phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This suggested patisiran can halt and reverse disease progression 82 . More recently, post hoc analyses of data from the phase 2 open-label extension and the phase 3 trial suggested that patients benefit from patisiran even when simultaneously receiving oral small-molecule TTR stabilizers (tafamidis or diflunisal) 83 .…”
Section: Lnpsmentioning
confidence: 99%
“…This suggested patisiran can halt and reverse disease progression 82 . More recently, post hoc analyses of data from the phase 2 open-label extension and the phase 3 trial suggested that patients benefit from patisiran even when simultaneously receiving oral small-molecule TTR stabilizers (tafamidis or diflunisal) 83 .…”
Section: Lnpsmentioning
confidence: 99%
“…Although the different treatment modalities may be complementary, there is limited evidence for the role of combination therapy. A post hoc analysis showed that patisiran efficacy and safety were similar with or without concomitant TTR stabilizer use, although this combination has not been explored further in clinical studies 88,89 . Similarly, other combinations of approved therapies (with, e.g., doxycycline, tauroursodeoxycholic acid, green tea, and other therapies) have yet to undergo rigorous clinical testing.…”
Section: Treatment Choice For Attrv Amyloidosis With Polyneuropathy I...mentioning
confidence: 99%
“…A post-hoc analysis of the phase II OLE and phase III trials compared patisiran alone and with concomitant use of a TTR stabilizer, either tafamidis or diflunisal. 37 During the phase II OLE, 26% of patients received patisiran alone, 48% of patients received tafamidis with patisiran, and 26% of patients received diflunisal with patisiran. Patients in the phase III APOLLO trial were on patisiran alone, but 33% had previously used tafamidis and 20% had previously used diflunisal.…”
Section: Post-hoc Analysis Of Patisiran Studiesmentioning
confidence: 99%